Decoupling of fluctuating power in single-phase systems through a symmetrical half-bridge circuit - Yi Tang; Blaabjerg, Frede; Poh Chiang Loh (2014 IEEE Applied Power Electronics Conference and Exposition - APEC 2014, 2014)
Single-phase AC/DC or DC/AC systems inherently subject to harmonic disturbance which is caused by the well-known double line frequency ripple power. This issue can be eased through the installation of bulky electrolytic capacitors in the dc-link, but such passive filtering approach may inevitably lead to low power density and limited system lifetime. An alternative approach is to use active power decoupling so that this ripple power can be diverted into other energy storage devices to gain improved system performance. Nevertheless, all existing active methods have to introduce extra inductors or film capacitors to store the ripple power, and this again leads to increased component costs. In view of this, this paper presents a symmetrical half-bridge circuit which utilizes the dc-link capacitors to absorb the ripple power, and the only additional components are a pair of switches and a small filtering inductor. A design example is presented and the proposed circuit concept is also verified with simulation and experimental results. It shows that at least ten times capacitance reduction can be achieved with the proposed active power decoupling method, which proves its effectiveness.